2021
DOI: 10.1016/j.jimonfin.2021.102459
|View full text |Cite
|
Sign up to set email alerts
|

Capital market financing and firm growth

Abstract: This paper studies whether there is a connection between finance and growth at the firm level. It employs a new dataset of 150,165 equity and bond issuances around the world, matched with income and balance sheet data for 62,653 listed firms in 65 countries over 1990-2016. Three main patterns emerge from the analyses. First, firms that choose to issue in capital markets use the funds raised to grow by enhancing their productive capabilities, increasing their tangible and intangible capital and the number of em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 127 publications
(109 reference statements)
1
11
0
1
Order By: Relevance
“…Substantial research demonstrates the indispensable link between capital markets and economic development [48,49]. The capital market plays a decisive role in resource allocation and provides an important channel for direct financing of enterprises.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial research demonstrates the indispensable link between capital markets and economic development [48,49]. The capital market plays a decisive role in resource allocation and provides an important channel for direct financing of enterprises.…”
Section: Discussionmentioning
confidence: 99%
“…The second group of articles investigates market information in relation to ESG data, such as stock return and price [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The third set of studies examines the incorporation of accounting and market data into a single model [12][13][14][15][16][17][36][37][38][39][40][41][42][43][44][45].…”
Section: -2-financial Company Performance and The Environmental Pilla...mentioning
confidence: 99%
“…Blundell et al (1995) propose using firmspecific 'level effects' based on historic patenting activity, and we follow this alternative to capture firm-level heterogeneity, including firm-level experience, absorptive capacity and other unobservables. Given the strong link found in the literature between innovation and financing (Didier et al, 2021), historic patenting activity allows us to control for those unobserved factors that could drive both access to finance and firm performance. Finally, we control for firm size given the importance and debated role firm size has on performance and access to capital markets: recent literature has in fact shown that smaller firms' faster growth than larger ones depends on their access to capital markets (Didier et al, 2016).…”
Section: Empirical Specification and Identificationmentioning
confidence: 99%